Optimizing The Role Of The Community In Managing Tourism Objects Of Lakey Hu'u Beach, Dompu Regency. - Johansah (Faculty of Economics and Business, University of Mataram, 2022)
Lakey tourist attraction is located in Hu'u District, Dompu Regency, this tourist attraction is known as one of the best surfing destinations in Indonesia and even the world. The development of tourism activities in the Lakey beach tourist attraction has provided benefits to the economic improvement of the people on the Lakey coast. This study discusses optimizing the role of the community in managing Lakey Beach tourism objects, Hu'u Village, Hu'u District, Dompu Regency. The results of the study are described in several answers to the problem formulation, namely optimizing the role of the community in managing Lakey Hu'u Beach attractions, Dompu Regency. The results of this study were presented with descriptive methods and SWOT analysis. The data collection techniques used in this study were observation, interviews, documentation, and literature study. Informants are the government, the Pokdarwis, and the community, and collect research evidence in the form of image documentation. The results show that the community tends to be dominated in the implementation stage, where the community plays a role in planning, giving ideas, the role of the community in contributing, the role of the community in the form of energy both in the form of maintaining cleanliness and in the form of maintaining security and comfort